Optimizing Spring-back and Spring-go in Vee-bending of SCGA340BHX Galvanized Steel: A Taguchi Approach (Jurnal Teknik Mesin Mechanical Xplore, 2025)
Spring-back and spring-go are critical elastic recovery phenomena in sheet metal forming that affect the angular precision of bent components. This study investigates the influence of punch angle, die opening, and punch speed on these behaviors during the Vee-bending process of SCGA340BHX high-strength galvanized steel. A Taguchi design of experiments with an L8 orthogonal array was applied, and spring-back angles were measured and analyzed using the “smaller-is-better” signal-to-noise (S/N) ratio criterion. The results reveal that punch angle is the most influential parameter governing spring-back and spring-go tendencies, followed by die opening and punch speed. A punch angle of 50° and a die opening of 35 mm produced the highest average spring-back (3.03°), while spring-go behavior was observed primarily at higher punch speeds (35–40 mm/min). The study further confirmed the inverse relationship between bending force and spring-back, with lower forming forces correlating to greater elastic recovery. These findings provide a comprehensive understanding of the interdependence between geometric and kinematic factors in elastic recovery phenomena, offering quantitative insights for optimizing Vee-bending operations involving thin, high-strength steel.